Analiza porównawcza województw ze względu na poziom rozwoju demograficznego - Gazińska, Mirosława (Comparative Analysis for Voivodships with Regard to Level of Demographic Development, 2005)
The aim of the paper is to classify new voivodships (i.e. after the administrative reform) in the years 1995-2002 from the point of view of selected demographic processes. The demographic development levels are analysed on the basis of three groups of diagnostic features: 1) population structure by age and sex, 2) mortality, and 3) marriage and procreative behaviours. The application of a synthetic measure leads to ordering voivodships with regard to demographic development in selected groups of diagnostic features and for all features in total.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 556-564